Education on Accident Prevention at School in Madrasah Aliyah Negeri 2 Serang City - Pertiwi, Wiwik Eko; Nurdiawati, Ela; Mujiyanti, Sri; Julianto, Octoberry (AMK : Abdi Masyarakat UIKA, 2024)
School is a place of work for teachers and a place to gain knowledge for students so it should be able to provide guarantees of safety, security and health. The aim of this research isto increase knowledge, understanding and build awareness target audience regarding the importance of efforts to prevent accidents at school for MAN 2 Serang City students. This research uses the methods of pretest and posttest. Research analysis using the t-test. The results of the research show that the p-value is 0.000, p<α so it can be concluded that there is a significant difference between knowledge before counseling and after counseling.